Virtual Reality for Future Education: Systematic Literature Review - Iwan Purnama; Menrisal; Nuridin Widya Pranoto; Ruth Rize Paas Megahati S (Jurnal Penelitian Pendidikan IPA, 2023)
The development of information and communication technology is very rapid at this time contributed greatly to the development process of various kinds of learning media based on the application of technology as one of the innovations in education, Virtual Reality (VR) technology itself is a way in a way perform the appearance of learning pictures in the form of media three-dimensional or what is usually better known as 3D. Where the purpose of research is to explain Virtual Reality for Future Education. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. Virtual Reality (VR) has the potential to enhance education by enabling greater learning potential than ever before, in addition to luring us into new realms. Learning can reach students' emotional core in novel and fascinating ways thanks to virtual reality. This study also states that learning subjects that can benefit the most from implementing Virtual Reality as learning media are science, social studies, and history. However, the potential is much greater. Â